Makna Simbolik Dalam Tradisi Manik Beladau Di Desa Rawak Hulu Kecamatan Sekadau Hulu Kabupaten Sekadau - Kurniawan, Hadi; Firmansyah, Andang; Mirzachaerulsyah, Edwin (Peneliti.net, 2024)
This research aims to determine the procession and symbolic meaning of the Manik Beladau tradition as well as efforts to preserve it in the Malay community in Rawak Hulu Village, Sekadau Hulu District, Sekadau Regency. Qualitative research with descriptive methods is the type of research that researchers use. Data collection was carried out through observation, interviews and documentation. The stages of data analysis include data collection, data reduction, data presentation, and verification/drawing conclusions. Then the data validity technique uses source triangulation and technical triangulation. The results of the research show that in the procession carrying out the manic Beladau tradition, it is divided into four processions, each of which contains a symbolic meaning, namely: 1. Sprinkling with flower water, which has a symbolic meaning to cleanse oneself of all the bad things that the newlywed couple has done in the past. . 2. Drinking fresh water has a symbolic meaning as a form of gratitude to Allah SWT. 3. Smoking the bride and groom has a symbolic meaning as a hope for protection. 4. Stepping on eggs and rice that have been coagulated has a symbolic meaning as a form of hope that all disease outbreaks that will threaten the bridal couple can be eliminated. Community leaders and the Rawak Hulu Village government synergize with each other to carry out their role as guides and motivators for the village community regarding the importance of cultural values in the Rawak Hulu area so that they continue to be preserved.